Dealing With Differences : Taking Action on Class, Race, Gender, and Dsability - Ellis, Angele; Liewellyn, Marilyn (Thousand Oaks, California : Crown Press, 1996)
Dealing With Differences is a classroom-tested action guide to dealing with issues and prejudice around class, race, gender, and disability. The exercises, discussion topics, and readings provide a framework to bring these complex issues out in the open as positive forces for change. Students share lived experiences to engage in active learning. Contains 48 lesson plans in 6 study units that can be used in any curriculum or advisory period. Motivate students' learning by providing Practical guidelines for group interaction Interactive exercises, discussion topics, and readings A list of resources needed to successfully implement Dealing With Differences Sample discussions and exercises that build engaged and thinking classrooms Activities that increase students' self-esteem, empathy, and understanding Opportunities for students to take action in their school and community Designed primarily as a supplemental program for use in high school classrooms, Dealing With Differences is useful for all teachers, administrators, and community members, as well as students and faculty of education. The exercises in this book will awaken teachers to the rich diversity in their own classrooms and help students gain insights about one another in a climate of mutual respect and trust "--Back cover
Includes bibliographical references.
Keywords: prejudices. -- Problems, exercises -- United States; individual difference -- Problems, exercises -- United States .; multiculturalism -- Study and teaching (Secondary) -- United States